2015
DOI: 10.1109/lpt.2014.2362939
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mg Doping in GaN Interlayer on the Performance of Green Light-Emitting Diodes

Abstract: A light-emitting diode (LED) structure containing a low-temperature (LT) GaN interlayer between active region and AlGaN electron blocking layer is proposed to improve the performance of InGaN-based green LEDs. The experimental and simulated results show that, as the Mg doping depth in the LT-GaN interlayer increases, the hole injection efficiency gets improved and electron current leakage decreases, while defectrelated nonradiative recombination increases. With an optimized Mg doping depth in the LT-GaN interl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…As the injection current increased from 0.01 to 350 mA, these samples showed a significant efficiency droop: the To evaluate the effect of the LT p-GaN layer on the efficiency droop in these three samples, the integrated EL intensity divided by the current, i.e., relative EQE, was plotted as a function of the injection current at 300 K, as shown in Figure 7. As the injection current increased from 0.01 to 350 mA, these samples showed a significant efficiency droop: the EQE first increased due to the gradual saturation of nonradiative recombination centers and then decreased (i.e., efficiency droop), mainly due to electron leakage [19,20]. To qualitatively compare the efficiency droop for the three samples, efficiency droop can be defined as follows:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the injection current increased from 0.01 to 350 mA, these samples showed a significant efficiency droop: the To evaluate the effect of the LT p-GaN layer on the efficiency droop in these three samples, the integrated EL intensity divided by the current, i.e., relative EQE, was plotted as a function of the injection current at 300 K, as shown in Figure 7. As the injection current increased from 0.01 to 350 mA, these samples showed a significant efficiency droop: the EQE first increased due to the gradual saturation of nonradiative recombination centers and then decreased (i.e., efficiency droop), mainly due to electron leakage [19,20]. To qualitatively compare the efficiency droop for the three samples, efficiency droop can be defined as follows:…”
Section: Resultsmentioning
confidence: 99%
“…Generally, efficiency droop is caused by two main factors: (i) a high content of In can generate structural defects acting as nonradiative recombination centers due to a large discrepancy in atomic size between indium (In) and gallium (Ga), and a large lattice mismatch of 11% between InN and GaN; (ii) a large lattice mismatch between the InGaN well layer with a high In content and the GaN barrier layer causes straininduced polarization, resulting in a strong quantum-confined Stark effect (QCSE) [15][16][17]. Previous studies showed that the introduction of a low-temperature (LT) p-GaN layer effectively improved the EL characteristics and reduced the efficiency droop in GaN-based blue LEDs [18][19][20][21]. Nevertheless, the effect of an LT p-GaN layer on longer-wavelength GaN-based LEDs has not been reported in detail, especially with different thicknesses of the LT p-GaN layer.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the need for efficient emitters in this spectral region is well acknowledged and has prompted intensive efforts in this direction, leading to optimizations of growth conditions, improvements to structure design and the use of alternative substrates among other techniques. For instance, the crystalline quality of high In-content QWs is improved by growing on nanorod-patterned GaN/Si templates, while the IQEs can be increased by controlling the growth temperatures to reduce point defect incorporation. , The introducing of interlayer and electron blocking layer also leads to a smoother band diagram and more uniform carrier distributions which enhances electroluminescence; , on the other hand, light output powers can be boosted with high-density ultrasmall In-rich quantum dots with good carrier confinement and reduced defects . The proposed device structure will benefit significantly from the success of these efforts.…”
Section: Resultsmentioning
confidence: 99%
“…These methods have brought blue InGaN/GaN LEDs with remarkable progress in IQE exceeding 80%. However, InGaN/GaN green LEDs with a high In content (25% green and 18% for blue) suffer a lower EQE than blue InGaN/GaN LEDs because of the “green gap” problem caused by the large difference in lattice constant and thermal expansion coefficient between high-In-content InGaN and GaN [ 11 , 12 ]. Several techniques such as deposition of Si-doped graded superlattice or InGaN/GaN superlattice between n-GaN and InGaN/GaN active region [ 1 , 13 ], low-temperature-grown GaN cap layer [ 14 ], and AlGaInN/GaN MQWs [ 15 ] were used to address this issue.…”
Section: Introductionmentioning
confidence: 99%